HE-4 in the Diagnosis of Carcinoma of Ovary Presented as Unknown primary Carcinoma: A Case Report - Shengmin Huang MD; Muhammad Tahir MD; Gardith Joseph MD; Richrd Wu MD; Jaron Tepper MD; Jen C. Wang MD (Journal of Investigative Medicine High Impact Case Reports)
Ovarian cancer is the second most common gynecologic malignancy in the United States, with high mortality due to delayed diagnosis. Serum CA-125 is widely used for screening and monitoring but lacks sensitivity and specificity in some cases. We present a 67-year-old female diagnosed with advanced-stage ovarian cancer despite normal CA-125 levels, with elevated HE4 (human epididymis protein 4), underscoring its diagnostic value. This case highlights the importance of integrating HE4 with CA-125 in ovarian cancer evaluation and emphasizes a multimodal approach to enhance early detection and outcomes.